Public Management of Communal Property: Best Practices for the Post-War Recovery of Ukraine - Pokotylo, Tetyana; Berezin, Andrii (Pressing Problems of Public Administration, 2024)
The article investigated the public management of communal property in the context of Ukraine’s post-war reconstruction. Special attention is paid to the analysis of national, international, and public initiatives aimed at restoring the destroyed infrastructure and ensuring the effective management of communal facilities. Different countries’ best practices and methods to restore communal property after conflicts and natural disasters were studied.After World War II, Germany received significant financial and technological aid under the Marshall Plan, which allowed for a rapid rebuilding of industry and infrastructure. Using the latest technologies and innovations contributed to increasing the efficiency and quality of restoration works. After the war, France developed its own Plan Monnet, which emphasized centralized planning and state regulation. The state actively coordinated the reconstruction process, providing financial and administrative resources. Post-war Japan achieved an “economic miracle” thanks to the implementation of effective economic reforms and the development of high-tech industry. Innovation and research have become critical elements of reconstruction.The article differed from other studies in its complexity and emphasis on the practical aspects of the implementation of restoration projects, in particular on the possibility of involving public-private partnerships and public initiatives. The key challenges faced by local self-government bodies were also considered, and specific recommendations were offered to improve the efficiency of communal property management in the post-war period. The conclusions of the article emphasized the need for coordinated efforts of all interested parties for the successful recovery and sustainable development of Ukraine.The results of this study can be used by the government, local authorities and public organizations to develop strategies and programs for the restoration of communal property. Implementation of effective management practices will contribute to faster and better reconstruction, increase of economic stability and improvement of the population’s well-being.